Application of remote sensing techniques for prediction of landslide hazard areas in Malaysia - Ahmad, Samsudin; Seeni Mohd., Mohd. Ibrahim; Hashim, Mazlan (2004)
Landslide hazard occurs mostly due to instability of terrain surface and directly related to several parameters such as surface temperature, land use type, terrain slope and underground water level. Remote sensing techniques have been widely used to study characteristics of land surface due to the advantage of repetitive data acquisition over wide areas in a short time. Spatial analysis using data derived from remote sensing technique and other thematic map data may facilitate greatly prediction and estimation of landslide hazard areas. In this paper landslide hazard carried out in the Genting Sempah are of Malaysia is presented. Landsat-TM satellite data have been used to derive land surface temperature and land use information. The elevation and terrain slope have been determine from Digital Elevation Model (DEM) generated from aerial photographs using stereo correlation techniques. Underground water level information has been estimated from the combination of the above data. From these data, simple algorithm were used to classify the area into different risk zones. By combining all the risk maps using spatial analysis techniques, a final risk map was produced which take into account all the above factors.